Swamedikasi, DAGUSIBU, dan Waspada Bahan Berbahaya Kosmetik: Pengabdian Masyarakat di Dusun Kepuhsari, Surakarta: Indonesia - Ainurofiq, Ahmad; Fatimi, Hana Anisa; Prabowo, Imam; Larasati, Rizky Dwi; Choiri, Syaiful; Az Zahro, Fatimah Aqilah; Usmarini, Razita Fathya; Maharani, Vania; Fauziah, Siva; Purbowati, Dwi; Rinaldi, Rafli; Jauhari, Muh Rizqi Fadlah (Jurnal Abdimas Madani dan Lestari (JAMALI), 2026)
Inappropriate self-medication limited public understanding of the DAGUSIBU (Dapatkan, Gunakan, Simpan, dan Buang) concept, and the widespread use of harmful cosmetic products remain major challenges in improving community health. This community service activity aimed to increase the knowledge of residents in Dusun Kepuhsari RW 38 regarding rational self-medication, proper application of the DAGUSIBU principle (Get, Use, Store, and Dispose of Medicine Correctly), and the risks associated with hazardous cosmetic ingredients. The activity was carried out through an educational and participatory approach consisting of a pretest, leaflet distribution, direct delivery of material by resource persons, interactive Q&A sessions, distribution of door prizes, and a posttest. The results showed an overall increase in participants' understanding across all three topics. Knowledge of self-medication increased by 1.2 times, while understanding of DAGUSIBU improved by 1.44 times. Education on harmful cosmetics also led to a significant improvement in participants' awareness of product legality, identification of dangerous substances, and associated health risks. Through this educational program, the community is expected to become more informed and responsible in using both medicines and cosmetics safely and wisely.